Cellulase Production from Filamentous Fungi for Its Application in the Hydrolysis of Wheat Straw. Issue 1763 (18th February 2015) - Toscano-Palomar, L.; Montero-Alpirez, G.; Stilianova-Stoytcheva, M.; Vertiz-Pelaez, E.; Romero Uscanga, y E.
ABSTRACT: Extended research has been developed in the use of wheat straw (WS) as biomass for the production of biofuels (bioethanol), including the processes of degradation of cellulose by enzymatic systems. For centuries, Cellulose has been used by man; however, its enormous potential as a renewable energy source was recognized only after the discovery of cellulose degrading enzymes (cellulases). A wide variety of microorganisms can produce cellulolytic enzymes under appropriate culture conditions and among these microorganisms are filamentous fungi of the genera Trichoderma, Aspergillus, Penicillium and Fusarium. The purpose of this study was to produce cellulase enzyme from previously isolated and characterized filamentous fungi. Cellulytic fungi belonged to Aspergillus flavus, Aspergillus niger, Aspergillus oryzae, Penicillium chrysogenum, Penicillium sp., and Trichoderma harzianum. All these strains were preserved by lyophilization and also kept in sterile media (sand and soil) at 4 °C. The production of cellulases by submerged fermentation was performed in a Mandels mineral medium. The nitrogen sources were urea and ammonium sulfate. Glucose alone was used in the pre-inoculum, and dried and ground wheat straw was used in the fermentation as carbon sources. Subcultures of spore suspensions were incubated with orbital stirring (120 rpm) at 30 °C for 48 hours and used as inoculum for submerged fermentation with wheat straw as substrate in mineral medium with an initial pH of 5. Activity cellulase was determined by the method of 3, 5-dinitrosalicylic acid (DNS). The results showed that wheat straw have potential for use as a substrate in the production of cellulases. Aspergillus niger showed the highest enzymatic activity from the cellulase produced 0.051 FPU (filter paper units) after 96 hours of fermentation.